The economics of the long period - Ponthière, Grégory ca. 20./21. Jh (Cambridge University Press, 2022)
This book provides a non-technical introduction to Unified Growth Theory (UGT), that is, the study of history as a succession of economic regimes. It first focuses on the canonical example of regime shift: the transition from the regime of Malthusian stagnation to the modern regime of sustained economic growth. Then, it broadens the perspectives on historical change by examining other regime shifts involving institutional and environmental forces. This book fills a gap in the market by providing a more accessible treatment of UGT and invites readers to explore ideas of continuity and discontinuity in history